Effect of Dy on electrochemical supercapacitive behaviour of α-MnO2 nanorods - Gangwar D.; Tiwari P.; Kumar A.; Prakash R.; Rath C. (My University, 2025)
α-MnO2 nanorods doped with different molar concentrations of Dysprosium (Dy) have been successfully synthesised via hydrothermal method as an electrode material. The electrochemical properties are evaluated using cyclic voltammetry, Galvanostatic charge discharge studies where we demonstrate an increase in capacitance with increase in Dy concentration. For α-MnO2: Dy (15 mol %), capacitance enhances by twice than that of bare α-MnO2. XRD (X-Ray diffraction) and FE-SEM (Field Emission- Scanning Electron Microscopy) measurements show that although the structure of Dy doped α-MnO2 remains tetragonal, the crystallinity degrades along with the reduction in aspect ratio of nanorods. In addition, BET (Brunauer-Emmett-Teller) measurement shows that the surface area and size of the pores increase with increase in Dy concentration. Poor crystallinity, large surface area and smaller nanorods are an evidence of high capacitance observed in α-MnO2: Dy (15 mol %). The effect of Dy concentration on structure, morphology, surface area and electrochemical properties are discussed in detail for the application of supercapacitor. © 2019 Elsevier Ltd